Audit Teknologi Informasi Untuk Mengoptimalkan Sumber Daya Dan Tata Kelola Teknologi Informasi - Siswaya; Rachmad Sanuri (Jurnal Informatika Komputer, Bisnis dan Manajemen, 2026)
This study evaluated the maturity of Information Technology (IT) governance at SMK Koperasi Yogyakarta using the COBIT 2019 framework to optimize the institution's IT resources. The assessment evaluation showed an overall maturity rating of 2.18 (Managed), indicating that although IT processes are functional and documented, they are still lacking standardization across the organization. The analysis identified a significant average gap of 0.82, with the most substantial deficiencies found in operational monitoring and IT unit personnel competency. Therefore, a strategic roadmap is proposed that focuses on policy formalization and staff development to transition the institution towards a more optimal, standardized, and efficient digital environment.